Intrauterine Hematoma in the First Trimester and Pregnancy Complications: A Systematic Review and Meta-Analysis - Qin, Zhao-juan; Xu, Yu; Du, Yi; Chen, Ya-li; Sun, Liang; Zheng, Ai (Frontiers in Medicine, 2022)
Background Studies evaluating the relationship between intrauterine hematoma in the first trimester and prenatal complications are conflicting. Objectives To evaluate whether intrauterine hematoma identified in the first trimester in women with singleton pregnancies is associated with adverse perinatal outcomes. Search Strategy A comprehensive literature search of three databases (Embase, PubMed, and Web of Science) was performed up to September 2021. Selection Criteria Cohort and case-control studies that have evaluated the relationship between intrauterine hematoma identified before 14 gestational weeks and the risk of prenatal complications, in women with a singleton pregnancy. Data Collection and Analysis Two members of our team independently assessed the studies for inclusion, collected the data of interest, and assessed the risk of bias, and calculated pooled odds ratios (ORs) using random-effects models. Main Results Nine studies, including 1,132 women with intrauterine hematoma and 11,179 controls met the inclusion criteria. Intrauterine hematoma increased the risk of spontaneous abortion [OR 2.15, 95% confidence interval (CI) 1.23–3.75], preterm birth (OR 1.83, 95% CI 1.37–2.43), fetal growth restriction (OR 2.33, 95% CI 1.13–4.83) and placental abruption (OR 3.16, 95% CI 1.23–8.13). No statistically significant association was found between intrauterine hematoma and preeclampsia (OR 1.30, 95% CI 0.87–1.94). Conclusion Intrauterine hematoma in the first trimester of pregnancy increases the risk of spontaneous abortion, preterm birth, placental abruption, and fetal growth restriction. Systematic Review Registration https://www.crd.york.ac.uk/PROSPERO/.